Dysfluencies in a multilingual speaker: A case study - Nel, Talitha; Geertsema, Salome; Le Roux, Mia; Alet Graham, Marien; Abdoola, Shabnam (Revista de Investigación en Logopedia, 2025)
Research involving a multilingual person who clutters and stutters in African languages is limited. Our aim was to describe the dysfluencies of a multilingual person with dysfluencies (PWD) across and within Sepedi, Afrikaans, and South African English (SAE). A single multilingual adult participant with a persistent mild stuttering and moderate cluttering pattern participated. A mixed-method cross-sectional design was implemented. Perceptual analysis was used to study stuttering-like dysfluencies (SLD) and cluttering-like dysfluencies (CLD) across and within the three languages. The results revealed that the most prevalent SLD in all three languages was the repetition of part words. The repetition of whole words was the most prevalent CLD. The plosive /d/ sound represented the highest occurrence and resulted in repetitions of sounds across and within Afrikaans and SAE. There were no repetitions of sounds in Sepedi, but three repetitions of the syllable /se-/ occurred. Future research is recommended to include a bigger sample size, and other African languages should also be considered.
Keywords: Cluttering; Dysfluencies; Multilingualism; Stuttering